Polemik Keagamaan dalam Tafsir Malja’ Aṭ-Ṭālibīn Karya K.H. Ahmad Sanusi - Jajang A Rohmana (SUHUF, 2017)
This article discusses some responses of Ahmad Sanusi (1888-1950) in Tafsir Malja’ Aṭ-Ṭālibīn toward religious polemic in Priangan in 1930s. Malja’ Aṭ-Ṭālibīn is Qur'anic exegesis in Sundanese Arabic script. Sanusi gave his critical response to the reformists criticism related to some khilafiyah (disputed) issues, such as tawaṣṣul (method in religious prayer by relating it to the pious man), reading surah al-Fātihah behind the imam, the congregation of wirid after ṣalat, usury, and some foods that are forbidden in Islam. Using critical discourse analysis, this study argues that Sanusi’s responses to some issues of religious polemic demonstrate the influence of his ideology of Ahl as-Sunnah wa al- -Jamā’ah (Sunni) vis a vis reformist criticism. His position was never separated from the line of Sunni tradition that tends to be more flexible in understanding the local traditions in Indonesian Archipelago. This study is significant in demonstrating the Sharia debate in Indonesia which is not only has a linkage with the heritage of classical jurisprudence in Islam as well as other areas, but also are considered to be in the edge or periphery of Islam that is constantly finding its own context. It is a religious polemic that contributes to the distinction of Islamic formation in Indonesia.